Ultra-Sensitive HIV-1 Latency Viral Outgrowth Assays Using Humanized Mice - Schmitt, Kimberly; Akkina, Ramesh (Frontiers in immunology, 2018)
In the current quest for a complete cure for HIV/AIDS, highly sensitive HIV-1 latency detection methods are critical to verify full viral eradication. Until now, the quantitative viral outgrowth assays (qVOA) have been the gold standard for assessing latent HIV-1 viral burden. However, these assays have been inadequate in detecting the presence of ultralow levels of latent virus in a number of patients who were initially thought to have been cured, but eventually showed viral rebound. In this context, new approaches utilizing mouse-based VOAs are promising. In the murine VOA (mVOA), large numbers of CD4 T cells or PBMC from aviremic subjects are xenografted into immunodeficient NSG mice, whereas in the humanized mouse-based VOA (hmVOA) patient CD4 T cell samples are injected into BLT or hu-hematopoetic stem cells (hu-HSC) humanized mice. While latent virus could be recovered in both of these systems, the hmVOA provides higher sensitivity than the mVOA using a fewer number of input cells. In contrast to the mVOA, the hmVOA provides a broader spectrum of highly susceptible HIV-1 target cells and enables newly engrafted cells to home into preformed human lymphoid organs where they can infect cells after viral activation. Hu-mice also allow for both xenograft- and allograft-driven cell expansions with less severe GvH providing a longer time frame for potential viral outgrowth from cells with a delayed latent viral activation. Based on these advantages, the hmVOA has great potential in playing an important role in HIV-1 latency and cure research.